Impact Investing and Community Development - Phillips, Ronald (Maine Policy Review, 2016)
The growing and worldwide practice called “impact investing”—investing capital for a social as well as financial return - is increasingly challenging private investors and managers of wealth, university endowments, mutual funds, foundations, pension funds, and individuals to direct capital in ways that contributes to the good of society. With roots in the 1960s civil rights era, the multi-billion dollar U.S. Community Development Corporations (CDCs) and Community Development Financial Institutions (CDFIs) industry can serve as a major vehicle for impact investors. CDCs/CDFIs raise and deploy private and public capital to benefit marginalized populations and regions of the country aspiring for economic opportunity. These entities create jobs in small businesses, produce affordable housing and facilities like child care, and help to build sustainable enterprises. Phillips presents the case that investing in CDCs/CDFIs ensures this new, untapped source of capital makes a difference for those in need.
Keywords: impact investing; community development; foundations